The regulation of IMF deposition in pectoralis major of fast- and slow- growing chickens at hatching - Lu Liu; Huanxian Cui; Ruiqi Fu; Maiqing Zheng; Ranran Liu; Guiping Zhao; Jie Wen (Journal of Animal Science and Biotechnology, 2017)
Abstract Background The lipid from egg yolk is largely consumed in supplying the energy for embryonic growth until hatching. The remaining lipid in the yolk sac is transported into the hatchling’s tissues. The gene expression profiles of fast- and slow-growing chickens, Arbor Acres (AA) and Beijing-You (BJY), were determined to identify global differentially expressed genes and enriched pathways related to lipid metabolism in the pectoralis major at hatching. Results Between these two breeds, the absolute and weight-specific amounts of total yolk energy (TYE) and intramuscular fat (IMF) content in pectoralis major of fast-growing chickens were significantly higher (P < 0.01, P < 0.01, P < 0.05, respectively) than those of the slow-growing breed. IMF content and u-TYE were significantly related (r = 0.9047, P < 0.01). Microarray analysis revealed that gene transcripts related to lipogenesis, including PPARG, RBP7, LPL, FABP4, THRSP, ACACA, ACSS1, DGAT2, and GK, were significantly more abundant in breast muscle of fast-growing chickens than in slow-growing chickens. Conversely, the abundance of transcripts of genes involved in fatty acid degradation and glycometabolism, including ACAT1, ACOX2, ACOX3, CPT1A, CPT2, DAK, APOO, FUT9, GCNT1, and B4GALT3, was significantly lower in fast-growing chickens. The results further indicated that the PPAR signaling pathway was directly involved in fat deposition in pectoralis major, and other upstream pathways (Hedgehog, TGF-beta, and cytokine–cytokine receptor interaction signaling pathways) play roles in its regulation of the expression of related genes. Conclusions Additional energy from the yolk sac is transported and deposited as IMF in the pectoralis major of chickens at hatching. Genes and pathways related to lipid metabolism (such as PPAR, Hedgehog, TGF-beta, and cytokine–cytokine receptor interaction signaling pathways) promote the deposition of IMF in the pectoralis major of fast-growing chickens compared with those that grow more slowly. These findings provide new insights into the molecular mechanisms underlying lipid metabolism and deposition in hatchling chickens.